Tell Shemshara 2018: Emerging and Floating Evidence - Eidem, J.; Merlino, M.; Mariotti, E.; Kalim Salih, R. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2019)
During 2016-17 high water levels of Lake Dokan effectively prevented new archaeological salvage work at Tell Shemshara, but in October 2018 the site was briefly accessible, and some urgent fieldwork could be conducted. This paper outlines some main results of this effort.